2009
DOI: 10.1007/s12517-009-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural activity and lithology on groundwater quality in the Merdja area, Tebessa, Algeria

Abstract: This work presents results of the hydrogeological and hydrochemical studies on groundwater samples from the alluvial aquifer of Merdja in Tébessa, located in the Western part of this town. Its groundwater resources are used mainly for crop irrigation in an agriculture dominated area. Hydrochemical and water quality data obtained through a sampling period (December 2008) and analysis program indicate that nitrate pollution can be a serious problem affecting groundwater due to the use of nitrogen (N) fertilizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…These authors have shown that the major sources of groundwater contamination are related to on-site sanitation, to the presence of solid waste dumpsites, including household waste pits, to infiltration of surface water, to agricultural activities, to the presence of petrol service stations (underground storage tanks), and to the mismanagement of well fields. Nitrate contamination of groundwater is a problem that commonly occurs in Africa, as illustrated in the studies for Algeria (Rouabhia et al, 2010;Messameh et al, 2014), Tunisia (Hamza et al, 2007;Anane et al, 2014), Morocco (Bricha et al, 2007;Fetouani et al, 2008;Benabbou et al, 2014), Senegal (Sall and Vanclooster, 2009;Diédhiou et al, 2012), Ivory Coast (Loko et al, 2013a;Eblin et al, 2014), Ghana (Tay and Kortatsi, 2008;Fianko et al, 2009), Nigeria (Wakida and Lerner, 2005;Akoteyon and Soladoye, 2011;Obinna et al, 2014), South Africa (Maherry et al, 2009;Musekiwa and Majola, 2013), Ethiopia (BGS, 2001a;Bonetto et al, 2005), and Zambia (Wakida and Lerner, 2005). Several of these studies showed that pollution from anthropogenic activities is the main source of high and variable nitrate levels.…”
Section: Introductionmentioning
confidence: 99%
“…These authors have shown that the major sources of groundwater contamination are related to on-site sanitation, to the presence of solid waste dumpsites, including household waste pits, to infiltration of surface water, to agricultural activities, to the presence of petrol service stations (underground storage tanks), and to the mismanagement of well fields. Nitrate contamination of groundwater is a problem that commonly occurs in Africa, as illustrated in the studies for Algeria (Rouabhia et al, 2010;Messameh et al, 2014), Tunisia (Hamza et al, 2007;Anane et al, 2014), Morocco (Bricha et al, 2007;Fetouani et al, 2008;Benabbou et al, 2014), Senegal (Sall and Vanclooster, 2009;Diédhiou et al, 2012), Ivory Coast (Loko et al, 2013a;Eblin et al, 2014), Ghana (Tay and Kortatsi, 2008;Fianko et al, 2009), Nigeria (Wakida and Lerner, 2005;Akoteyon and Soladoye, 2011;Obinna et al, 2014), South Africa (Maherry et al, 2009;Musekiwa and Majola, 2013), Ethiopia (BGS, 2001a;Bonetto et al, 2005), and Zambia (Wakida and Lerner, 2005). Several of these studies showed that pollution from anthropogenic activities is the main source of high and variable nitrate levels.…”
Section: Introductionmentioning
confidence: 99%
“…High salinity water cannot be used on soils with limited drainage system. With adequate drainage, this class can be used if special management practices for salinity control are taken, and plants with high salt tolerance are grown (Abdel-Fattah and Helmy, 2015;Rouabhia et al, 2009). According to the Gupta et al (1999), water of EC between 0.30 and 1.44 dSm -1 can be used for irrigation with most crops grown on most soils with little likelihood of soil salinity (Gupta, 1990).…”
Section: Salinity Hazardmentioning
confidence: 99%
“…Excessive application of fertilizers produces soil and groundwater contamination through percolation and leaching [ 5 , 6 ]. The degree of leaching depends on a number of factors, including management practices, soil type and corresponding leaching potential, rainfall, and land use [ 7 ].…”
Section: Introductionmentioning
confidence: 99%